2007
DOI: 10.1107/s090744490705531x
|View full text |Cite
|
Sign up to set email alerts
|

Surprises and pitfalls arising from (pseudo)symmetry

Abstract: The presence of pseudosymmetry can cause problems in structure determination and refinement. The relevant background and representative examples are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 67 publications
3
112
0
Order By: Relevance
“…Our final refined model contained two nearly identical molecules in the asymmetric unit at positions (x, y, z) and (x + 1/2, y, z), with the (x + 1/2, y, z) molecule demonstrating rotational disorder (PDB entry 3ks1; Robbins et al, 2010). Zwart et al (2008) described a crystallographic scenario that can occur when such an observation is made. In the monoclinic P2 1 case with a pseudo-translational operator (x + 1/2, y, z), the unit cell consists of four molecules [A (x, y, z), B (x + 1/2, y, z), C (Àx + 1/2, y + 1/2, Àz) and D (Àx, y + 1/2, Àz)].…”
Section: Introductionmentioning
confidence: 99%
“…Our final refined model contained two nearly identical molecules in the asymmetric unit at positions (x, y, z) and (x + 1/2, y, z), with the (x + 1/2, y, z) molecule demonstrating rotational disorder (PDB entry 3ks1; Robbins et al, 2010). Zwart et al (2008) described a crystallographic scenario that can occur when such an observation is made. In the monoclinic P2 1 case with a pseudo-translational operator (x + 1/2, y, z), the unit cell consists of four molecules [A (x, y, z), B (x + 1/2, y, z), C (Àx + 1/2, y + 1/2, Àz) and D (Àx, y + 1/2, Àz)].…”
Section: Introductionmentioning
confidence: 99%
“…Data were reduced by using HKL2000 (25) and TRUNCATE (26). Analysis of the data with phenix.xtriage from the PHENIX suite (27) revealed that the crystal was merohedrally twinned. As the crystal was found to be isomorphous to those described previously (24), direct refinement of the existing model (PDB accession code 3FSN) against the higher resolution dataset was performed with REFMAC5 (28).…”
Section: Purification Of Cross-linked Products and Identification Ofmentioning
confidence: 99%
“…Crystals of RPE65 obtained in the presence of racemic emixustat belonged to space group P6 5 22 with 1 monomer in the asymmetric unit, whereas crystals containing (R)-or (S)-emixustat or MB-002 belonged to space group P6 5 with 2 monomers in the asymmetric unit. The absence of twinning was determined with phenix.xtraige (59).…”
Section: 0mentioning
confidence: 99%